QUALITY OF CHICKEN EGGS ISA BROWN 18-22 WEEKS AGE POST VACINATION EGG DROP SYNDROME AND GIVEN RANGE OF DIFFERENT AMOUNT - N. K. E., Sumayani,; Dewi, G. A. M. K.; Kencana, G. A. Y. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
Egg drop syndrome causes a decrease in the quality and quantity of eggs so it does not benefit farmers. The research was conducted at the Faculty of Animal Science, Bukit Jimbaran Campus, and egg quality tested every week in the Poultry Laboratory of the Faculty of Animal Science, Sudirman Campus, Denpasar, which lasted for 5 weeks. The study sample was used by Isa Brown laying hens on an average age of 18 weeks. The study design used a completely randomized design (CRD) consisting of 3 treatments and 5 replications. Each replication consisted of 3 laying 1 control hens of Isa Brown so that the total chickens used were 45 tails.The treatment of this study was R 1 :Chicken Isa Brown without a vaccine candidate and given a commercial ration of 80 g/head/day, R 2 :Chicken with candidates for the EDS vaccine and given a commercial ration of 80 g/head/day R 3 :Chicken with candidates vaccine EDS and given 84 g/head/day of commercial ration. The variables observed were egg weight, egg index, shell weight, shell thickness, egg yolk color, pH and, haugh unit. The results showed that treatment R 2 and R 3 (P<0,05) were able to increase egg weight, eggshell weight, eggshell thickness, egg yolk color and haugh unit compared to treatment R 0 but there was a decrease in egg shape index, egg pH on R 2 treatment. Based on the results of the study it can be concluded that the quality and quantity of R 3 eggs is higher than the treatment of R 2 in chiken egss Isa Brown aged 18-22 week.   Keywords : Isa Brown, quality of eggs, rations, vaccine candidates, egg drop syndrome